Predictors and outcomes of TLE via femoral vein bailout. (14th October 2021) - Shafir, Y; Massalha, E; Milman, A; Luria, D; Glikson, M; Sabbag, A; Beinart, R; Nof, E; Leshem, E
Abstract: Background: Transvenous Lead Extraction (TLE) is usually performed via a superior approach. Predictors and outcomes of TLE via femoral vein bailout are ill defined. Methods: A single tertiary center cohort of 426 consecutive patients who underwent TLE between May 2010 and February 2020 were analyzed. Venography was routinely performed before system upgrade to identify occluded veins. Patients were divided into 2 groups on the basis of the need for femoral bailout extraction. Predictors for TLE requiring femoral bailout and outcomes were analysed. Results: A total of 928 leads were extracted and femoral bailout approach was needed in 49 patients (11.5%). A higher proportion of RV leads required femoral bailout approach [51/499 (10.2%)]. Femoral bailout was more common among younger patients, longer lead dwell time, more pocket entries, higher number of extracted leads, presence of abandoned leads [14/49 (28.6%)], and among patients with occluded veins [10/22 (45.5%)]. The presence of abandoned leads, vascular occlusion and age remained a significant predictor for femoral bailout in multivariate analysis. Femoral bailout TLE resulted in a relatively higher rate of major complications [5/49 (10.2%) vs 9/377 (2.4%); p=0.02) but had no related intra-procedural mortality (0/3) and no additional 30 day mortality [2/49 (4.1%) vs 33/377 (8.8%); p=0.4]. Conclusion: TLE of abandoned leads, occluded veins and younger age were found to be predictors of femoral bailout requirement. Despite higher rates of major complications in femoral TLE bailout this did not result in increased mortality. Venography before TLE should be considered for procedure planning. Funding Acknowledgement: Type of funding sources: None.